TRANSFORMASI TATA RUANG DESA MELALUI PEMETAAN GEOSPASIAL BATAS DUSUN BERBASIS ARCGIS - Azhar Baihaky, Muhammad; Maulana, Yoga Chandra; Supratno, Setyo (An-Nizam, 2025)
Mapping village boundaries is a crucial activity in the management and administration of rural areas, often facing challenges related to accuracy and clarity of boundary lines. This community service focuses on mapping the boundaries of Dusun Ridomanah using ArcGIS software to enhance the accuracy and effectiveness of land management. The process begins with the collection of geographic data through field observations and GPS techniques, followed by data processing using ArcGIS to produce detailed boundary maps. Subsequently, the obtained data is analyzed and discussed with local residents to ensure the accuracy and suitability of the map with real-world conditions. The outcome of this mapping is a digital boundary map that not only improves the precision of geographic information but also supports village administration in development planning, land dispute resolution, and more effective resource management. This finding demonstrates that the use of ArcGIS significantly enhances mapping quality and provides tangible benefits to the local community. This community service is expected to serve as a model for mapping initiatives in other rural areas.